The human placenta releases substances that drive lung cancer into apoptosis - Zabel Peter; Hauber Hans-Peter; Abdullah Mahdi; Kähler Daniel; Schultz Holger; Zeiser Tobias; Marwitz Sebastian; Vollmer Ekkehard; Goldmann Torsten (BMC, 2009)
Abstract Background As there is no optimal treatment of non small cell lung cancer due to its resistance to common chemotherapeutics, we investigated the effect of human placenta-conditioned medium on tumor tissue. The human placenta constitutes a mixture of maternal and fetal origin and displays a variety of immunomodulatory aspects. Methods Freshly resected non small cell lung cancer tissues were incubated with placenta-conditioned medium in a short-term tissue culture model and A549 cells were challenged, respectively. Term placenta was used for producing conditioned medium and HOPE-fixed stimulated tumor tissue was analyzed for expression of caspase-3 and Ki67 via immunohistochemistry. The effects of conditioned medium on squamous cell carcinoma were further compared to physiological concentrations of Carboplat/Gemzar. Results Conditioned medium caused in 2 of 3 cases elevated expression of caspase-3 and reduced expression of Ki67 in 3 out of 3 cases, while the chemotherapeutic agents caused no comparable expression of caspase-3 or reduction of Ki67. In cell culture up to 50% of karyopyknosis was investigated and even sterile-filtrated medium caused widespread reduction of Ki67 on protein level. Conclusion Human placenta releases substances that mediate apoptosis and reduce proliferation in tumor tissue and cell culture. As even sterile-filtrated medium caused the mentioned effects we hypothesize one or more soluble mediators. The detailed way of promoting apoptosis and nature of these mediators need to be elucidated in further studies.